Triggered single-photon emitters based on stimulated parametric scattering in weakly nonlinear systems - Kyriienko, Oleksandr (2015)
We introduce a scheme of single-photon emission based on four-wave mixing in a three mode system with weak Kerr-type nonlinearity. A highly populated lower energy mode results in strong stimulated scattering of particle pairs out of the central mode, which consequently limits the central mode occupation. Thus, the system can be reduced to a χ(2) nonlinear medium with greatly enhanced interaction constant. As a model setup we consider dipolaritons in semiconductor microcavities. Using the master equation approach we show strong antibunching under continuous-wave pump, which largely exceeds the conventional blockade mechanism. Finally, using a pulsed excitation we demonstrate theoretically a triggered single-photon emitter in a weakly nonlinear system with 33% emission probability.